2022
DOI: 10.14238/pi62.5.2022.341-56
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and stunting in children aged 6-23 months in rural Sumba, Indonesia

Abstract: Background Linear growth retardation in the first two years of life leads to numerous harmful consequences. Lack of diversity in the diet and inadequate amounts of complementary food have been associated with stunted growth in children. Objective To assess the dietary intake and investigate for associations with stunting among children aged 6-23 months. Methods This case-control study compared the dietary intake of children aged 6-23 months with and without stunting in the South and West Wewewa sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Although studies on the relationship between nutrient intake and stunting have differing results, children whose nutritional needs are not met over a long period will likely experience malnutrition. 8,9,12 In our study, the intake of energy and macronutrients was significantly lower in the stunted group than in the non-stunted group.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Although studies on the relationship between nutrient intake and stunting have differing results, children whose nutritional needs are not met over a long period will likely experience malnutrition. 8,9,12 In our study, the intake of energy and macronutrients was significantly lower in the stunted group than in the non-stunted group.…”
Section: Discussionmentioning
confidence: 40%
“…11 Studies on macronutrient intake have shown an inconclusive relationship with the incidence of stunting. 12,13 Slum areas go hand in hand with low income and nutritional problems in children. However, several studies in various Indonesian regions reported that there are many children with normal nutritional status in areas with low incomes.…”
mentioning
confidence: 99%
“…Another study also suggested no significant effect of protein intake on HAZ scores in subjects in the rural area of Sumba (p = 0.06) (Limardi et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…10 Penelitian juga menunjukkan bahwa sumber makanan hewani dapat mencegah kejadian stunting pada anak karena protein hewani berperan dalam mengoptimalkan pertumbuhan dan perkembangan sel-sel organ tubuh dengan baik, memperbaiki sel tubuh yang mengalami kerusakan, dan meningkatkan daya tahan tubuh. 16,30 Cara pemberian makan yang tepat juga berpengaruh terhadap asupan nutrisi pada anak. Memberikan makanan dengan cara yang terlalu mengekang dapat membuat anak trauma dan menolak makan, sedangkan memberikan makanan dengan cara yang terlalu memanjakan juga dapat menyebabkan anak menolak makan.…”
Section: Pemberian Makan Pada Anakunclassified